1998
DOI: 10.1046/j.1365-2672.1997.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus helveticus heterogeneity in natural cheese starters: the diversity in phenotypic characteristics

Abstract: The study of wild strains from natural habitats is a useful means of understanding better the heterogeneity within a species of biotechnological importance, and of obtaining atypical isolates with unknown capabilities. In the present research carried out on different Lactobacillus helveticus strains isolated from natural cheese starters, it was observed that several biotechnologically important characteristics can differ greatly between strains. Biotypes were found which differ in terms of fructose, maltose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
51
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 2 publications
10
51
0
1
Order By: Relevance
“…This confirmed that the genetic differences between Grana and Provolone cheese isolates not only depend on the differences in the conserved 16S rDNA region or in the plasmid profiles observed previously (14) but also are more widely distributed along the genome. This result is very interesting because it confirms at a genetic level the extensive phenotypic differences between the two groups of L. helveticus isolates reported previously (9,10). Sequencing data for L. helveticus isolates did not reveal extensive differences between the 16S rRNA gene sequences and the sequences of the species included in the GenBank database.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This confirmed that the genetic differences between Grana and Provolone cheese isolates not only depend on the differences in the conserved 16S rDNA region or in the plasmid profiles observed previously (14) but also are more widely distributed along the genome. This result is very interesting because it confirms at a genetic level the extensive phenotypic differences between the two groups of L. helveticus isolates reported previously (9,10). Sequencing data for L. helveticus isolates did not reveal extensive differences between the 16S rRNA gene sequences and the sequences of the species included in the GenBank database.…”
Section: Discussionsupporting
confidence: 89%
“…lactis, and Lactobacillus fermentum, and many biotypes (13, 27) of these species. Substantial differences in several technologically important characteristics have been found among L. helveticus strains isolated from natural dairy starter cultures (1,2,8,9,11,16,18,19,21,28,31).Because of the widespread use of L. helveticus in cheese technology, information concerning genotypic heterogeneity in this species is accumulating rapidly (6,7,14,17). A variety of genotypic and phenotypic methods have been used to show that the dominant L. helveticus communities in various dairy starters are composed of different biotypes, which sometimes may be associated with the source of isolation (2,6,9,12,14,20,22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…helveticus strains show phenotypic and genotypic variability (7,8,10,11). Fortina et al (7) reported that a wide phenotypic variability exists among L. helveticus strains isolated from natural cheese starters.…”
mentioning
confidence: 99%